Performance Evaluation of AODV with Varying Network Size in MANET Using Entity Models - Preeti (International Journal of Computer Sciences and Engineering, 2014)
A Mobile Ad-Hoc Network (MANET) is self-configuring network of mobile nodes connected by wireless links to form an arbitrary network topology without the use of existing Infrastructure. MANETs are characterized by multi-hop wireless connectivity, a frequently changing network topology and the need for efficient dynamic routing protocols plays an important role. Severe routing protocols targeted specifically at this environment have been developed and some performance simulations are made on a mature routing protocol i.e. Ad hoc On-Demand Distance Vector Routing. In this paper we perform extensive simulations using network simulator considering four performance metrics. For experiment purposes and to determine the impact of network size on the performance of this routing protocol we considered three different entity mobility models namely Random Direction (RD), Random Walk (RW) and Gauss Markov (GM) models with rectangular area sizes 1000 × 1000 m2. These three Mobility Models are selected to represent the possibility of practical applications in future. Our framework aims to evaluate the impact of different mobility models on the performance of MANET routing protocols.